Влияние уровня возбуждения на люминесценцию сульфида кадмия - Олешко В. И. Владимир Иванович; Корепанов В. И. Владимир Иванович; Лисицын В. М. Виктор Михайлович; Вильчинская С. С. Светлана Сергеевна (2007, 2007)
В фонде НТБ ТПУ отсутствует